2019
DOI: 10.31160/jotci201927a20190019
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound study of forearm arteries in patients undergoing cardiac catheterization, and assessment of predictors of arterial vessel caliber

Abstract: Background: The radial approach has been increasingly used worldwide for diagnostic and therapeutic cardiac catheterization. The radial artery caliber is one of the limitations of its use. The objective of this study was to describe the anatomy of the radial and ulnar arteries, as well as to develop a radial artery diameter prediction score using clinical and anthropometric criteria. Methods: Using vascular ultrasound with bilateral radial and ulnar artery measurements, 1,180 patients who underwent cardiac cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Evaluation of the size of the radial artery demonstrated that female sex is a predictor of arteries of smaller caliber. 12,13 The use of the pain criterion, despite being the most appropriate, may lead to a greater manifestation of pain in patients with arteries of caliber smaller than the material used, which may explain the higher incidence of RAS in women. The presence of circulating estrogen can also attenuate the effect of nitroglycerin, since estrogen has an important vasodilating role mediated by endogenous release of nitric oxide, normally maintaining a reduced vascular tone, with little response to the application of external nitrates.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the size of the radial artery demonstrated that female sex is a predictor of arteries of smaller caliber. 12,13 The use of the pain criterion, despite being the most appropriate, may lead to a greater manifestation of pain in patients with arteries of caliber smaller than the material used, which may explain the higher incidence of RAS in women. The presence of circulating estrogen can also attenuate the effect of nitroglycerin, since estrogen has an important vasodilating role mediated by endogenous release of nitric oxide, normally maintaining a reduced vascular tone, with little response to the application of external nitrates.…”
Section: Discussionmentioning
confidence: 99%